Hubungan Konsep Diri dan Kecerdasan Sosial dengan Keterampilan Berbicara Bahasa Indonesia Siswa SMA Diponegoro 1 Jakarta - Prima Dwi Yuliani (Indonesian Journal of Applied Linguistics Review, 2017)
The objective of the research was to know whether there are (1) correlations between self-concept and speaking Indonesian laguage skills, (2) social intelligence and speaking Indonesian laguage skills, (3) between self-concept and social intelligence with speaking Indonesian laguage skills simultaneously. This research was conducted at XI grade in SMA Diponegoro 1 Jakarta. The samples of this research were 40 students. This research were using survey method of regression analitic and correlational technique.The results of the research conclude that (1) there were positive and significant correlation between self-concept (X1) and speaking Indonesian laguage skills (Y) with ry1 is 0,914 and regression equation is Ŷ = 6,441 + 0,110X1; (2) there were positive and significant correlation between social intelligence (X2) and speaking Indonesian laguage skills (Y) with ry2 is 0,941 and regression equation is Ŷ = 9,577 + 0,075X2; and (3) there were positive and significant correlation between self-concept (X1) and social intelligence (X2) with speaking Indonesian laguage skills (Y) with ry12 is 0,959 and regression equation is Ŷ = 7,578 + 0,046X1 + 0,049X2. The results of this research conclude that there is a significant relationship between (1) self-concept and speaking Indonesian laguage skills, (2) social intelligence and speaking Indonesian laguage skills, (3) self- concept and social intelligence with speaking Indonesian language skills simultaneously